Przesłanki ekstradycyjne w prawie polskim: [Prerequisites of extradition in the Polish law] (Studia Prawnicze / The Legal Studies, 2023)
The article ennumerates extradition prerequisites provided for by the Polish law in force. In extradition law there are two points of reference: interior extradition law (the provisions of the code of penal proceedings and the Article 118 of the penal code) and international agreements, which distinctly fall into two groups: those signed before and after the Second World War (with socialist countries). Both types of regulations are mutually exclusive: the agreement between the states excludes the application of interior law with regard to matters covered by the provisions of the former. This indicates firstly that interior regulations settle the questions not provided for by an agreement, secondly, that the interior law can serve as sufficient grounds for extradition if it is impossible by virtue of an international agreement.The Polish law of extradition embraces the following prerequisites: the extraditable nature of offences, amenability to punishment of an act in the claiming country and the one summoned to extradite, appropriate age level of a fugitive (provided by the agreement), admissibility of prosecution (the existence of premises to take action) in the countries concerned,, necessity to substantiate a charge (in Poland explicitly provided so only in the treaties signed with the USA and Great Britain), the offence is not of political nature (this prerequisite does not appear in agreements signed with the socialist countries), the extraditable is not of Polish nationality or has not been granted political asylum, an offence has not been committed in the territory of the Polish People’s Republic.The extradition prerequisites may be of either absolute (the ascertainment makes extradition impossible) or relative nature (can be referred to as grounds for a claim to be rejected). According to the provisions of the code of penal proceedings only Polish nationality or asylum granted by the Polish People’s Republic are distinctly the impedements of absolute nature. In the article an opinion has been expressed that since the Article 11 of the code of penal proceedings does not provide the prerequisites of legal process, then extradition is inadmissible. In the agreements signed by Poland the greater number of premises are of absolute nature, i.e. they concern an obligatory extradition first of all.Moreover the premises may be removable (by the action of the summoned state) or not. In Polish jurisdiction the removable ones comprise: the impedement of nationality (when it was obtained otherwise them by birth) and territorial asylum (in author’s opinion — under all circumstances).